Analysis of the world experience of economic and mathematical modeling of smart enterprises - Madykh, A.A.; Okhten, O.O.; Dasiv, A.F. (Економіка промисловості, 2017)
The paper shows the inevitability of technological mode shift driven by the Industry 4.0, which implies the ubiquitous implementation of information technology, total automation of various processes and creation of cyber-physical systems with artificial intelligence. This requires a complete restructuring of manufacturing systems and production relations, especially in the economies of those countries that want to take a decent place in the new international division of labour of the digital future. An analysis of the world experience of such changes connected with smart industrialization, digital transformations of the economy, the emergence of the industrial Internet of Things and big data processing made it possible to draw the conclusion that it is necessary to apply economic and mathematical methods to justify the expediency of such transformations: economic validity, as well as physical viability of newly created systems. The use of the apparatus of economic and mathematical modeling allows studying properties of the smart system that is being designed, evaluating its effectiveness and risks, anticipating the emergence of problems and errors - without the risk of incurring significant losses which is inevitable when making direct changes in the object of research.Therefore, the purpose of this paper is to study the world experience in the economic and mathematical modeling of smart enterprises and to substantiate its use in the conditions of Ukraine.The review of publications, reflecting the aspects of economic and mathematical modeling in these areas, allowed to conclude that the methodical and methodological apparatus for modeling these processes is unsystematic and inefficient, as well as to formulate recommendations on the economic and mathematical modeling of smart enterprises in Ukraine. In order to take into account the specific features of Ukraine's technological and institutional development, a number of economic and mathematical modeling tools based on the use of production functions, models of inter-branch balance, network optimization models and simulation models based on stochastic dependencies were offered to support the creation of smart enterprises. Показано неминучість зміни технологічного укладу у зв'язку з промисловою революцією 4.0, що потребує кардинальної перебудови системи виробництва і виробничих відносин. У результаті аналізу зарубіжного досвіду подібних змін, пов'язаних зі смарт-індустріалізацією, цифровими трансформаціями економіки, становленням промислового інтернету речей, обробки великих даних, встановлено необхідність застосування економіко-математичних методів для обґрунтування доцільності подібних трансформацій: як пов'язаної з їх економічною обґрунтованістю, так і з фізичною життєздатністю новостворюваних систем. Огляд публікацій, які відображають аспекти економіко-математичного моделювання в зазначених сферах, дозволив зробити висновок про несистемність і неопрацьованість методичного і методологічного апарату моделювання даних процесів, а також сформулювати рекомендації щодо економіко-математичного моделювання смарт-підприємств в Україні. Для врахування особливостей технологічного та інституційного розвитку України при обґрунтуванні створення смарт-підприємств запропоновано ряд інструментів економіко-математичного моделювання, заснованих на використанні виробничих функцій, моделей міжгалузевого балансу, мережевих оптимізаційних моделей, імітаційних моделей на базі стохастичних залежностей. Показана неизбежность смены технологического уклада в связи с промышленной революцией 4.0, что требует кардинальной перестройки системы производства и производственных отношений. В результате анализа зарубежного опыта подобных изменений, связанных со смарт-индустриализацией, цифровыми трансформациями экономики, становлением промышленного интернета вещей, обработки больших данных установлена необходимость применения экономико-математических методов для обоснования целесообразности подобных трансформаций: как связанной с их экономической обоснованностью, так и с физической жизнеспособностью вновь создаваемых систем. Обзор публикаций, отражающих аспекты экономико-математического моделирования в перечисленных сферах, позволил сделать вывод о несистемности и непроработанности методического и методологического аппарата моделирования данных процессов, а также сформулировать рекомендации по экономико-математическому моделированию смарт-предприятий в Украине. Для учёта особенностей технологического и институционального развития Украины при обосновании создания смарт-предприятий предложен ряд инструментов экономико-математического моделирования, основанных на использовании производственных функций, моделей межотраслевого баланса, сетевых оптимизационных моделей, имитационных моделей на базе стохастических зависимостей.